Multiwavelength Observations of the very high energy Blazar 1ES2344+514 - Acciari, V. A. (2011)
Multiwavelength observations of the high-frequency-peaked blazar 1ES 2344+514 were performed from October 2007 to January 2008. The campaign represents the first contemporanous data on the object at very high energy (VHE, E > 100 GeV) gamma-ray, X-ray, and UV energies. Observations with VERITAS in VHE gamma-rays yield a strong detection of 20 sigmas with 633 excess events in a total exposure of 18.1 hours live-time. A strong VHE gamma-ray flare on December 7, 2007 is measured at F(>300 GeV) = (6.76 ± 0.62) × 10^-11 cm^-2 s^-1 , corresponding to 48% of the Crab Nebula flux. Excluding this flaring episode, nightly variability at lower fluxes is observed with a time-averaged mean of F(>300 GeV) = (1.06 ± 0.09) × 10^-11 cm^-2 s^-1 (7.6% of the Crab Nebula flux). The differential photon spectrum between 390 GeV and 8.3 TeV for the time-averaged observations excluding December 7, 2007 is well described by a power law with a photon index of 2.78 ± 0.09 (stat) ± 0.15 (syst). A slightly harder photon index of 2.43 ± 0.22stat ± 0.15syst is measured on the flaring night of December 7, 2007. Over the full period of VERITAS observations contemporaneous X-ray and UV data were taken with Swift and RXTE. Variability by a factor of ~7 is evident in the 2-10 keV flux between nightly observations. On December 8, 2007 the highest ever observed X-ray flux from 1ES 2344+514 was measured by Swift XRT at a flux of F(2-10 keV) = (6.58 ± 0.37) × 10^-11 erg cm^-2 s^-1. Evidence for a correlation between the X-ray flux and VHE gamma-ray flux on nightly time-scales is indicated with a Pearson correlation coefficient of r = 0.60 ± 0.11. Contemporaneous spectral energy distributions (SEDs) of 1ES 2344+514 are presented for two distinct flux states. A one-zone synchrotron self-Compton (SSC) model describes both SEDs using parameters consistent with previous SSC modeling of 1ES 2344+514 from non-contemporaneous observations.